Effects of an exercise program during three years in obese boys: an intervention study - Yolanda Escalante; Antonio García-Hermoso; Ana M. Domínguez; José M. Saavedra (FEADEF, 2013)
The aim of this study was to determine the effect of a long-term exercise program (3 years) on kinanthopometric and metabolic in obese children. The sample consisted of eight boys between 8 and 11 years, who conducted a aerobic multi-sport exercise program (three sessions, 90 minutes per week). Carried out an assessment kinanthropometric assessing the following parameters: height, weight, body mass index (BMI), zBMI, fat mass and fat free mass, and a metabolic assessing: total cholesterol (TC), HDL cholesterol, LDL cholesterol, triglycerides (TG), insuline, glucose, Homeostasis Model Assessment (HOMA-IR), ratio LDL/HDL and TC/HDL. Following the intervention, changes were observed on zBMI (ceasing to be obese after the intervention), total cholesterol, LDL, and ratio total cholesterol/HDL) and glucose levels at the long term, showing that longitudinal interventions generate positive benefits on obese children mainly in the lipid profile.